Development Of Literacy In Al Iman Islamic Elementary School - Eko Prasetyo Nurbudi Wiranto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This research aims to find out the development of literacy in elementary school students,especially in Integrated Islamic Elementary School Al Iman Magelang in the evensemester of the 2020/2021 school year. The approach in this study is qualitative researchwith descriptive methods, while the data retrieval process uses interview and observationtechniques. The subjects of the study were principals, students, teachers, and schoollibrary officers. Data analysis is done by reducing the data that has been collected. Data isprocessed by taking a qualitative approach to answering research questions. Based onresearch that has been done, the development of children's literacy at Al Iman MagelangIntegrated Islamic Elementary School is managed by the library in collaboration withclassroom teachers, extras and parents. Literacy development is carried out during thelearning process and supported by extracurricular activities. The activities carried out tosupport literacy include reading 15 minutes before learning, retelling readings that havebeen read at home, reading corners in the classroom, literacy competitions, visits toregional libraries and so on. Special attention is given to students who are low in literacyskills by providing opportunities to represent the classroom in the literacy race, this isdone so that confidence in children can be grown.